2000
DOI: 10.1590/1809-43922000304664
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva do Camarão Macrobrachium brasiliense (Heller, 1862) (Crustacea: Decapoda: Palaemonidae) em Igarapés de terra firme da Amazônia Peruana

Abstract: RESUMO -Foi estudada a biologia reprodutiva de Macrobrachium brasiliense (Decapoda: Palaemonidae) com base em 2604 indivíduos coletados entre outubro de 1994 e agosto de 1995, em dois igarapés de terra firme da estrada Iquitos-Nauta, Loreto (Amazônia peruana). A proporção sexual fêmea: macho foi de 1,7:1 sendo que as fêmeas foram um pouco mais abundantes que os machos durante todo o período de coleta. M. brasiliense apresentou dimorfismo sexual no comprimento cefalotorácico, sendo as fêmeas ligeiramente menore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
3
9
0
5
Order By: Relevance
“…Although M. amazonicum captured in Santana Island and Mazagão presents lower fecundity than those species; it has higher fecundity than M. lanchesteri with 58-580 eggs (Phone et al 2005), M. hainanense with 20-75 eggs (Mantel and Dudgeon 2005), M. brasiliense (Heller 1862) with 15-168 eggs (Garcia-Dávila et al 2000) among other Macrobrachium species reported by Lobão et al (1986) whose absolute fecundity is lower than 200 eggs.…”
Section: Discussionmentioning
confidence: 81%
“…Although M. amazonicum captured in Santana Island and Mazagão presents lower fecundity than those species; it has higher fecundity than M. lanchesteri with 58-580 eggs (Phone et al 2005), M. hainanense with 20-75 eggs (Mantel and Dudgeon 2005), M. brasiliense (Heller 1862) with 15-168 eggs (Garcia-Dávila et al 2000) among other Macrobrachium species reported by Lobão et al (1986) whose absolute fecundity is lower than 200 eggs.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, M. surinamicum has small size and produce much more eggs than the other Macrobrachium prawns with similar sizes, whose absolute fecundity is lower than 200 eggs (Phone et al 2005;Mantel and Dudgeon 2005;Garcia-Dávila et al 2000).…”
Section: Discussionmentioning
confidence: 87%
“…The species is distributed in 11 states of the Brazilian territory, and in Colombia, Venezuela, the Guianas, and Peru (Coelho & Ramos‐Porto, ; Holthuis, ; Melo, ; Pileggi, Magalhães, Bond‐Buckup, & Mantelatto, ). Most studies of M. brasiliense addressed its population ecology (García‐Davílla, Alcantara, Vasquez, & Chujandama, ; Mantelatto & Barbosa, ; Oliveira, Sant'anna, & Hattori, ), and there are few published distribution records (García‐Davílla & Magalhães, ; Santos, Castro, & Magalhães, ). Despite the species' wide distribution, there have been few taxonomic reviews (Coelho & Ramos‐Porto, ; Pileggi & Mantelatto, ) and few studies of other aspects of the species' biology such as behavior (Nogueira, Costa, & Almeida, ), feeding behavior (Melo & Nakagaki, ), mass‐length relationships or other measures of physiological condition (Taddei et al, ), reproductive potential (Oliveira, Sant'anna, & Hattori, ), or larval morphology (Pantaleão, Gregatti, Taddei, & Costa, ).…”
Section: Introductionmentioning
confidence: 99%